Theoretical analysis of project method application in teaching students of construction specialties a foreign language in a technical university - O. B. Simonova; V. K. Barashyan (Вестник Майкопского государственного технологического университета, 2023)
The article provides theoretical and practical justification for the effectiveness of project method application in teaching students of construction specialties in a technical university. The relevance of the research is determined by changes in the pace and paradigms of social life, transformation of the demands of students and employers, to which higher education has to respond, looking for new, innovative methods in relation to vocational education.The purpose of the research is to prove the effectiveness of project method application in teaching «Foreign Language» in relation to construction specialties through a theoretical generalization of the material on the chosen topic. The authors also set a goal to prove that the described methodology helps students to better navigate their future profession, since the project method is designed to combine theoretical and practical components of the educational process. Domestic and foreign literature on the selected topic have been analyzed, which has formed the basis of the research. Using empirical and theoretical research methods, the authors have managed to substantiate the relevance of the project methodology application in higher education, as well as using quantitative, statistical data processing methods to mathematically prove the effectiveness of the project method technology stated in the hypothesis, note the universality of the technology and the possibility of embedding in any educational field.